CORPORATION CRIMINAL RESPONSIBILITY MODEL BASED ON RESTORATIVE JUSTICE APPROACH IN INDONESIA - Pujiyono Pujiyono (Fakultas Hukum, Universitas Diponegoro, 2016)
Based on delinquiry non-potes doctrine, perpetrator and criminal responsibility are done by human (natuurlijk persoonen). Modernity can not be avoided by the development of corporation function. A research is needed to be conducted to answer questions whether criminal law is effective to overcome corporate crime and which corporation criminal responsibility model that can keep the balance of the protection of society and corporation interests through restorative justice approach. This study focuses on finding a win-win solution model of corporation criminal responsibility policy to keep the balance of the protection of society and corporation interests. This study used normative juridical method based on the secondary data,. The result of this research shows that criminal law with its retributive approach and its action which focus on the perpetrator is ineffective to handle corporate crime, because it ignores the victim To overcome those problems, corporation criminal responsibility model based on restorative justice approach in the form of “dual track system selective” is introduced. Keywords: Criminal Responsibility, Corporation and Restorative Justice